Multiresistance to antibiotics of Salmonella enterica serovar Typhimurium strains producing extended spectrum beta-lactamases (ESBLs) - Coculescu, BI (J Med Life, 2014)
The purpose of the study is to give the rising incidence of Salmonellosis and the continuous decrease of sensitivity of Salmonella to a range of antibiotics, the prime importance of the choice of optimal anti-infective chemotherapy in order to prevent the selection of multidrug-resistant strains (MDR). We have studied 54 strains of Salmonella sent for further investigation to “Cantacuzino” NIRDMI Bucharest. The statistical analysis was based on the interpretation pathogen susceptibility and analyzed according to CLSI recommendations 2009, which revealed that 8 (14,81%) identified as S. enterica serovar Typhimurium group, presented a phenomenon of MDR. S. Typhimurium strains producing ESBL showed resistance mechanisms associated with beta-lactam resistance to aminoglycosides, quinolones, sulfonamides and tetracyclines.